2023
DOI: 10.3390/math11051113
|View full text |Cite
|
Sign up to set email alerts
|

Deviance and Pearson Residuals-Based Control Charts with Different Link Functions for Monitoring Logistic Regression Profiles: An Application to COVID-19 Data

Abstract: In statistical process control, the control charts are an effective tool to monitor the process. When the process is examined based on an exponential family distributed response variable along with a single explanatory variable, the generalized linear model (GLM) provides better estimates and GLM-based charts are preferred. This study is designed to propose GLM-based control charts using different link functions (i.e., logit, probit, c-log-log, and cauchit) with the binary response variable. The Pearson residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The Random Forest model used in this study was evaluated, for each of the target variables, using ten (10) metrics -coefficient of determination (R 2 ) (Piepho, 2018;Jones, 2019;Hawinkel et al, 2024), the mean squared error (MSE) (Das et al, 2004;Kato & Hotta, 2021;Kim et al, 2021;Jin & Montúfar, 2023), the root mean squared error (RMSE) (Zollanvari & Dougherty, 2013;Busch et al, 2014;Huang et al, 2017;Belliardo & Giovannetti, 2020;Zhu, 2022;Reiter & Werner, 2024), the mean absolute error (MAE) (De Myttenaere et al, 2015aQi et al, 2020a, b;Baumgärtner et al, 2023;Wang et al, 2023;Xie, 2024), the mean absolute percentage error (MAPE) (De Myttenaere et al, 2015b), the maximum error (ME) (Lingasubramanian et al, 2011), the mean pinball loss (MPL) (Sluijterman et al, 2024), the mean gamma deviance (MGD) (Cheema et al, 2023), the mean Poisson deviance (MPD) (Oliveira et al, 2023) and the mean Tweedie deviance (MTD) (Wüthrich & Merz, 2023).…”
Section: Random Forest Model Evaluationmentioning
confidence: 99%
“…The Random Forest model used in this study was evaluated, for each of the target variables, using ten (10) metrics -coefficient of determination (R 2 ) (Piepho, 2018;Jones, 2019;Hawinkel et al, 2024), the mean squared error (MSE) (Das et al, 2004;Kato & Hotta, 2021;Kim et al, 2021;Jin & Montúfar, 2023), the root mean squared error (RMSE) (Zollanvari & Dougherty, 2013;Busch et al, 2014;Huang et al, 2017;Belliardo & Giovannetti, 2020;Zhu, 2022;Reiter & Werner, 2024), the mean absolute error (MAE) (De Myttenaere et al, 2015aQi et al, 2020a, b;Baumgärtner et al, 2023;Wang et al, 2023;Xie, 2024), the mean absolute percentage error (MAPE) (De Myttenaere et al, 2015b), the maximum error (ME) (Lingasubramanian et al, 2011), the mean pinball loss (MPL) (Sluijterman et al, 2024), the mean gamma deviance (MGD) (Cheema et al, 2023), the mean Poisson deviance (MPD) (Oliveira et al, 2023) and the mean Tweedie deviance (MTD) (Wüthrich & Merz, 2023).…”
Section: Random Forest Model Evaluationmentioning
confidence: 99%
“…[19][20][21][22] Furthermore, in the context of COVID-19 death monitoring by using control charts following studies proposed different charts and identified death patterns. [23][24][25][26][27] Medical information determines control chart classification. There may be continuous, count, or attribute-based data.…”
Section: Introductionmentioning
confidence: 99%
“…[19–22] Furthermore, in the context of COVID-19 death monitoring by using control charts following studies proposed different charts and identified death patterns. [23–27]…”
Section: Introductionmentioning
confidence: 99%
“…The paper authored by Cheema et al [2] studies GLM-based control charts using different link functions (i.e., logit, probit, c-log-log, and cauchit) with the binary response variable. The Pearson residuals (PR)-and deviance residuals (DR)-based control charts for logistic regression are proposed under different link functions.…”
mentioning
confidence: 99%